2019
DOI: 10.1016/j.jobcr.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Subgingivally delivered coenzyme Q10 in the treatment of chronic periodontitis among smokers: A randomized, controlled clinical study

Abstract: Background: Coenzyme Q10 is an antioxidant whose efficacy in periodontal diseases is well known. However studies regarding its efficacy in smokers with periodontitis are few. Coenzyme Q10 serves as an endogenous antioxidant and its increased concentration in the diseased gingiva effectively suppresses advanced periodontal inflammation.Objectives: The aim of this study is to evaluate the efficacy of coenzyme Q10 as an adjunct to scaling and root planing in smokers with chronic periodontitis. Methods: Total of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…Although similar in structure to vitamin K, CoQ10 is not a vitamin since it is naturally synthesized in every cell in the human body, whereas vitamins must be obtained from the diet [ 45 , 46 ]. Some studies have investigated the effects of CoQ10 in diabetes being a safe material with very low toxicity [ 47 , 48 , 49 ] while other studies have shown that oral application of CoQ10 is effective in improving periodontitis [ 50 , 51 , 52 , 53 ]. However, the local effect of CoQ10 in bone regeneration and healing of extraction sockets in humans have not been previously studied.…”
Section: Discussionmentioning
confidence: 99%
“…Although similar in structure to vitamin K, CoQ10 is not a vitamin since it is naturally synthesized in every cell in the human body, whereas vitamins must be obtained from the diet [ 45 , 46 ]. Some studies have investigated the effects of CoQ10 in diabetes being a safe material with very low toxicity [ 47 , 48 , 49 ] while other studies have shown that oral application of CoQ10 is effective in improving periodontitis [ 50 , 51 , 52 , 53 ]. However, the local effect of CoQ10 in bone regeneration and healing of extraction sockets in humans have not been previously studied.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Raut et al . [ 15 ] compared the evaluation of CoQ gel and Melaleuca alternifolia (tea tree oil) and concluded that both of these agents have equal effective antioxidant property, but not superior to SRP alone. Another study by Sharma et al .…”
Section: Discussionmentioning
confidence: 99%
“…This double action of CoQ10 could be the reason for its effect being equivalent to that of triamcinolone. Topical CoQ10 has been previously investigated in other oral conditions, such as periodontal and gingival conditions and showed a great clinical reduction in the in ammatory condition after a few weeks (Prakash et 2010, Darweesh et al, 2015, Raut et al, 2019, Pranam et al 2020.…”
Section: Discussionmentioning
confidence: 99%